Lithium rich clays in the Miocene volcano-sedimentary formations of Karlovassi Basin, Samos Island, E. Aegean, Greece - Ioannis Marantos; Panagiotis Paschos; Dimitrios Galanakis; Chrysanthi Ioakim; Nikolaos Xirokostas; Dimitrios Tarenidis; Georgios E. Christidis (Applied Clay Science, 2026)

Using dorsal fin spine sections to investigate the age and growth of devil firefish Pterois miles in the eastern Mediterranean (Cretan and Ionian Seas) - Georgios Christidis; Panagiota Peristeraki; Evangelos Tzanatos; George Tserpes; Amalia Giannakaki; Manolis Metaxakis; Aris Tsiroglou; Stylianos Somarakis (Frontiers in Marine Science, 2026)
Studies on Pterois miles growth in the Mediterranean Sea are scant, while otoliths, traditionally used to age Pterois species, present difficulties in sampling, handling and interpretation. In this study a total of 617 P. miles specimens collected from the Cretan and Ionian Seas were aged by reading transverse sections of the third dorsal spine. The monthly evolution of the spine’s edge type (hyaline or opaque) and marginal increment analysis supported the annual formation of annuli. Lionfish age ranged from 0 to 5 years. The length-on-spine radius relationship exhibited a significant change in slope indicating that beyond the estimated inflection point fish growth was slower in relation to spine growth. We applied a multi-stage body proportional back-calculation formula that accounted for this shift in the length-on-spine radius relationship. The comparison of von Bertalanffy growth curves fitted to back-calculated length-at-age data, confirmed the sexually dimorphic growth of Pterois , with males reaching higher mean lengths-at-age. Growth was faster off the island of Crete, which could be attributed to higher temperatures compared to the Ionian Sea. Published growth data from the Pterois invaded areas revealed that the growth performance was significantly lower in the Mediterranean compared to the Atlantic. Finally, an inverse ‘Rosa Lee phenomenon’ was observed, with mean back-calculated length at each annulus formation increasing with age. A hypothesis is formulated asserting that slow growing individuals experience higher mortality (‘faster is better’ hypothesis), which can be attributed to cooler winter temperatures and an associated energetic stress which is inversely related to fish size.

Spatial and temporal variability of surface dust concentration in western Crete (Greece) – Development of a monitoring network - Simon Bitzan; Fabian Kirsten; Georgios E. Christidis; Pagona Makri; Kerstin Schepanski (Aeolian Research, 2025)

Reduced mean annual precipitation immediately after the onset of the Paleocene-Eocene Thermal Maximum in the Bighorn Basin (Wyoming, USA) - Yanxiao Xu; Chaowen Wang; Kaipeng Ji; Hanlie Hong; Thomas J. Algeo; Georgios E. Christidis; Chenlei Zhao; Lucas J. Lourens; Philip D. Gingerich; Hemmo A. Abels (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

New records of rarely reported species in the Mediterranean Sea (March 2025) - JOSÉ CARLOS BÁEZ; OKAN AKYOL; ERNESTO AZZURRO; PIETRO BATTAGLIA; ANGEL BELMONTE-GALLEGOS; GEORGIOS CHRISTIDIS; FABIO CROCETTA; CEM DALYAN; YUNUS GÖNÜL; FABIO GRATI; SILVESTRO GRECO; CHRYSOULA GUBILI; et al. (Mediterranean Marine Science, 2025)
This collective study presents information on fifteen (15) species recorded across five countries (Greece, Italy, Slovenia, Spain, and Türkiye) and four (4) ecoregions, ranging from the Alboran Sea to the Aegean Sea. The recorded species belong to three phyla: Mollusca (3 species), Arthropoda (3 species), and Chordata (9 species). Among mollusks, Martadoris mediterranea is reported for the first time in the Aegean Sea at two different locations, while Opisthoteuthis calypso and Octopoteuthis sicula are newly recorded in the western Mediterranean. Regarding arthropods, Ocypode cursor is reported from the Tyrrhenian coast of Sicily, Pachygrapsus transversus is recorded for the first time in the Tyrrhenian Sea, and Cancer pagurus in the Sea of Marmara. Among chordates, Lobotes surinamensis and Zu cristatus are newly recorded in the Alboran Sea, while Callionymus fasciatus and Symphodus doderleini are reported from Slovenian coastal waters. Tripterygion delaisi and Gymnothorax unicolor are documented for the first time in the waters of the Sea of Marmara and Crete, respectively. Additionally, new records of rarely reported fish species include Arctozenus risso, Chromogobius zebratus, and Epinephelus aeneus in Turkish, Spanish, and Italian waters, respectively.

The diet and feeding habits of Lagocephalus sceleratus in the eastern Mediterranean: A case study carried out off the island of Crete (southern Greece) - RITA GOMES V.C.; GEORGIOS CHRISTIDIS; PANAGIOTA PERISTERAKI; STYLIANOS SOMARAKIS; GEORGE TSERPES (Mediterranean Marine Science, 2025)
This study focused on the diet and feeding habits of the invasive pufferfish Lagocephalus sceleratus in the coastal waters of Crete (Cretan and Libyan Sea, eastern Mediterranean). The diet was composed of a wide variety of organisms, while the number of specimens with empty gastrointestinal tracts was low (14.41%). In total we were able to identify 38 different species of fish and invertebrates within the tracts analysed. Fish were the main diet component, followed by crustaceans and mollusks (mostly gastropods and cephalopods). At family level, the most significant preys were Sparidae and Mullidae teleosts, along with Cavoliniidae gastropods. The trophic level of L. sceleratus was estimated to be 4.13. The trophic niche breadth was intermediate, whereas the L. sceleratus population exhibits a mixed feeding strategy. Spatiotemporal differences in diet composition were also identified. The application of generalized additive models (GAMs) revealed that depth at which the fish were captured, season, region and total length, were significant predictors of the probability of occurrence of its most frequent prey groups. Fish prey occurrence was more probable in autumn and summer and at circa 20-25 m depth. In contrast, the probability of consuming crustaceans was higher in spring and winter and in specimens measuring 450-500 mm in length, and lower at 20-25 m, whilst increasing until a maximum at 40 m. The probability of non-cephalopod mollusks consumption was higher in winter and in the Libyan Sea, as well as at greater depths. Fish size had a significant effect on the likelihood of consuming photosynthetic organisms (algae and seagrass) and cephalopods, which was higher in larger fish. This study presents further evidence of the negative impact of L. sceleratus on the fisheries sector, revealing both predation on commercial species and the ingestion of various fishing gear parts.

Another One Bites the Net: Assessing the Economic Impacts of Lagocephalus sceleratus on Small-Scale Fisheries in Greece - Georgios Christidis; Stratos Batziakas; Panagiota Peristeraki; Evangelos Tzanatos; Stylianos Somarakis; George Tserpes (Fishes, 2024)
The assessment of the economic impacts of marine invasive species is fundamental for adopting mitigation measures, yet such impacts have been underreported in the Mediterranean Sea. The silver-cheeked toadfish (Lagocephalus sceleratus) is a toxic pufferfish that since its introduction has seriously disturbed small-scale fisheries along the eastern Mediterranean coast. This species depredates on fishing gears, causing damage to nets, longlines and commercial catches. To quantify its economic impact on small-scale fisheries, we interviewed 141 fishers from Crete (Cretan and Libyan Sea) and the Ionian Sea (Greece) during May 2020–December 2022. The mean annual economic cost resulting from L. sceleratus depredation was estimated at EUR 6315 ± 2620 per vessel in Crete and EUR 258 ± 120 in the Ionian Sea. Additionally, observer surveys carried out on board small-scale fishing vessels in Crete showed that depredation probability was significantly influenced by fishing depth, sea surface temperature, gear type (nets, longlines) and region (Cretan, Libyan Sea). L. sceleratus was caught more frequently and in higher numbers in the Libyan Sea. In response to depredation, fishers in Crete have altered their fishing tactics in terms of fishing in deeper waters, reducing fishing time and changing the technical characteristics of fishing gears. Our results underscore the adverse impacts of L. sceleratus on Greek small-scale fishers, emphasizing the need for region-specific management plans where the species establishes large populations.

Multi-analytical characterisation of wheat biominerals: impact of methods of extraction on the mineralogy and chemistry of phytoliths - Nafsika C. Andriopoulou; Georgios E. Christidis (Archaeological and Anthropological Sciences, 2020)